Effects of single-port laparoscopic percutaneous extraperitoneal closure on the orientation of the vas deferens and testicular perfusion and volume: Experience from a single center. Issue 3 (June 2016) - Li, Canqiang; Xu, Le; Peng, Yonghui; Liang, Xuankun; Lin, Weibin
Summary: Objective: To investigate the influence of single-port laparoscopic percutaneous extraperitoneal closure (LPEC) on the orientation of the vas deferens and testicular perfusion and volume in pediatric patients undergoing inguinal hernia repair. Methods: A total of 92 consecutively enrolled boys preoperatively diagnosed with a unilateral inguinal hernia underwent single-port LPEC between June 2013 and June 2014. The orientation of the vas deferens and the testicular perfusion and volume of these patients were ultrasonographically assessed preoperatively, one month after surgery and six months after surgery. Results: The surgical procedures were performed successfully without conversion or serious perioperative complications. Ultrasonography showed no angulation or distortion of the vas deferens on the surgical side during a six-month follow-up period. Similarly, there were no perioperative changes in testicular perfusion or volume. Conclusion: Our experience suggests that the single-port LPEC technique can be safe and effective in pediatric patients with an inguinal hernia and that this technique does not affect the orientation of the vas deferens or testicular perfusion or volume. Figure Suturing was performed extraperitoneally.